The Effect Of Current Ratio And Debt To Equity Ratio On Stock Returns: Case Study on Infrastructure Sector Companies listed on the Indonesia Stock Exchange in 2023 - Yurinisa, Alifa; Susanto, Heri; Fitrianti, Dewi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of the study was to determine the effect of Current Ratio and Debt to Equity Ratio on Stock Returns in Infrastructure sector companies listed on the Indonesia Stock Exchange in 2023. The research method uses qualitative research. Collection techniques with documentation methods obtained from internet information. Data analysis using multicollinearity, Multiple Linear Regression, Heteroscedasticity, Autocorrelation Test. Based on the results of data analysis, it can be concluded that the highest Current Ratio value is owned by NRCA, and the lowest is owned by JSMR, WSKT, WIKA, BUKK, and EXCL. The highest Debt to Equity Ratio value is owned by WSKT, WIKA, and ACST, and the lowest is owned by GOLD. The highest Stock Return is owned by CASS, ISAT, and JSMR, and the lowest is owned by BUKK. Current Ratio and Debt to Equity Ratio simultaneously affect Stock Returns. Keywords: Current Ratio, Debt to Equity Ratio, Stock Return.